(untitled) (Journal of the College of Basic Education, 2022)
Mural art is one of the most important subjects of art education on the one hand and a methodological material in institutes of fine arts on the other hand. And faster so that the student can absorb all the information presented to him in an interesting way. Based on the foregoing, the problem of the current research can be summarized by the following question: What is the effect of teaching with the aesthetic approach to developing skill performance in the art of murals for female students of the Institute of Fine Arts? The research aims to identify the effect of teaching with the aesthetic approach to developing the skill performance in the subject of mural art for female students of the Institute of Fine Arts. The research community consists of the students of the Department of Fine Arts / Institute of Fine Arts - Diyala for Girls - Morning Studies and the Institute of Fine Arts Baghdad / Karkh for girls who, their number (12) who study the subject of mural art, as the number of students in this department in the two institutes reached (114) students With (70) female students at the Institute of Fine Arts in Diyala and (44) female students at the Institute of Fine Arts in Baghdad Al-Karkh, they are divided into (3) academic stages for the academic year (2021-2022). The most important results are: After applying Cohen’s equation, the following was found: The effect size of the cognitive achievement test was (5,332). Therefore, the effect size of teaching with the aesthetic approach on cognitive achievement has a significant impact on the students of the experimental group. The effect size of the skill performance test was (2,904). Therefore, the effect size of teaching with the aesthetic approach on the skill performance has a significant impact on the students of the experimental group. The most important conclusions are: 1- The steps of the educational content of the study plans in the subject of mural art contributed to the process of attracting the attention of (experimental) students to the topics that were taught according to the aesthetic approach, which stimulated the students’ motivation to complete the requirements of the educational material. 2- Distinguishing the educational content of the study plans designed according to the aesthetic approach in a simplified manner that facilitated the process of acquiring educational experiences in the subject of mural art after conducting a process of simplifying the concepts and information contained in this subject.